Alih Wahana Cerpen Yabu no Naka karya Akutagawa Ryunosuke ke dalam film Rashomon karya Akira Kurosaswa - Jayanira, Dina; Anita Dewi, Ni Made Andry; Ari Sulatri, Ni Luh Putu (Humanis, 2017)
The aims of this study is to find out the changes between the short story Yabu no Naka by Akutagawa Ryunosuke into the film Rashomon by Akira Kurosawa in terms of characters and background of the place. This study uses descriptive method of the vehicle switch analysis. Technical analysis of the data used in this study is to read, understand, analyze, compare, analyze changes between the short story Yabu no Naka by Akutagawa Ryunosuke into the film Rashomon by Akira Kurosawa. Results of the discussion in this study indicate that there are changes that occur in the short story Yabu no Naka work of Ryunosuke Akutagawa once into the film Rashomon by Akira Kurosawa. Shape changes that occur are: 1) cutting which includes the reduction of character and background subtraction place there on the short story Yabu no Naka by Akutagawa Ryunosuke 2) the addition that includes the addition of a character and development background in the film Rashomon by Akira Kurosawa.
Keywords: vehicle switch, cutting, addition, Yabu no naka, Rashomon